DESIGN AND DEVELOPMENT OF WIRELESSHART ADAPTER FOR REAL TIME INDUSTRIAL PROCESS MONITORING AND CONTROL APPLICATION - SUPRAMANIAM, THASARATHARAO (2019)
Recent advances in wireless technologies such as WirelessHART has prompted the applications of inexpensive technologies to industrial monitoring and control application.